The European Union’s Relations with Greenland - Tomala, Magdalena (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
Greenland has a special relationship with the European Union due to its link with the Kingdom of Denmark – Greenland’s mother country. As a result, Greenland shares some parts of the EU’s internal market via association agreements. Greenland, has become a meeting place of American, European and Asian interests in the Arctic. It is therefore essential that the EU doesn’t lose the North and keeps strengthening its relationship with Greenland. After having focused its attention on the East and the South, it is high time that the European Union looks further North, notably through a more ambitious Arctic Window in its Northern sphere of influence.